2020
DOI: 10.1002/app.50375
|View full text |Cite
|
Sign up to set email alerts
|

Pentaerythritol derived phosphorous based bicyclic compounds as promising flame retardants for thermoplastic polyurethane films

Abstract: Imparting flame retardancy without melt dripping in thermoplastic polyurethane (TPU) is a challenging task. In the current work, a series of pentaerythritol derived phosphorous based flame retardants (FRs labeled FR1, FR2, FR3, and FR4) were synthesized, and their suitability for TPU thin films (<100 micron) was explored. Vertical flammability tests revealed that a blend of FR2 and TPU at 2% phosphorous content exhibited excellent flame suppression and complete stoppage of melt dripping whereas samples prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…However, due to the release of large amounts of corrosive gases and toxic fumes during combustion, which causes serious harm to human health and the environment, the use of these FRs is prohibited or discouraged. To address these challenges, there has been a renewed focus on designing halogen-free flame retardants in recent years. …”
Section: Introductionmentioning
confidence: 99%
“…However, due to the release of large amounts of corrosive gases and toxic fumes during combustion, which causes serious harm to human health and the environment, the use of these FRs is prohibited or discouraged. To address these challenges, there has been a renewed focus on designing halogen-free flame retardants in recent years. …”
Section: Introductionmentioning
confidence: 99%
“…They observed that the weight ratio of PDTBP and APP was 1:2 with 30 wt % loading, the HDPE/IFR composites could have a limiting oxygen index value of 30.8% and attained -94 V-0 rating. 15 In order to improve the flame retardant performance of different kinds of polymeric systems, 2,6,7trioxa-1-phosphabicyclo[2.2.2]octan-4-methanol-1-oxide (PEPA) and its variations have been the subject of multiple reports in recent times 28,29,30,31 . However, there hasn't been any research done on the usage of PEPA derivatives as a polymer for thermoplastic polyurethane yet.…”
mentioning
confidence: 99%